Modelling of the competitive activities of qualified female short-distance runners, taking into account their individual characteristics - Vrublevskiy, E. P.; Sevdalev, S. V.; Lashkevich, S. V.; Gerkusov, A. S. (Physical Education of Students, 2019)
Purpose: to develop an individual model of competitive activity of qualified female runners to achieve the planned sports result of 100 m. Material: for qualified athletes (n = 88), using video-computer analysis, individual characteristics of speed dynamics in running for 100m and kinematic parameters of running for different distances were recorded. The tensodynamograms of the manifestation of the strength of muscle groups carrying the main load in the structure of the sprint run of 18 short-distance runners of various qualifications were recorded and processed. Results: promising models of competitive activity in the 100m race for the planned sports result have been developed. Based on the model of a specific athlete, the main areas of work are determined, means and methods of training effects are selected. Conclusions: Practical realization of the developed model provided the necessary increase in indicators. This made it possible for female athletes (n = 8, age 19-21 years) to improve the average result in running the main distance (compared with the previous year) by 0.18 s.